Collagen fibril diameter distribution affects permeability of ligament tissue: A computational study on healthy and injured tissues. (November 2020) - Erisken, C.; Tsiantis, A.; Papathanasiou, T.D.; Karvelas, E.G.
Highlights: Micropolar theory for the investigation of the fluid flow inside ligament tissues. Collagen fibril diameter and diameter distribution of healthy and injured ligament tissues. Investigation of the variability of the diameter distribution between healthy and injured ACL tissues on the hydraulic permeability. Lower hydraulic permeability in the injured ligament tissues compared to the healthy one. Abstract: Background and objective In avascular or hypovascular tissues, elements required for maintaining tissue functions are recruited through diffusion, which is highly related with the permeability of the extracellular matrix in health and injury. Here, we investigate the effect of collagen fibril diameter distribution of bovine Anterior Cruciate Ligament (ACL) tissue on the hydraulic permeability of the matrix. Based on the fact that the diameter distribution is significantly different between healthy and injured ACL tissues, our study aims to investigate the effect of such variability on the hydraulic permeability. Methods Simulations are carried out in 3 D geometries reconstructed from actual collagen filament/fibril diameter distributions obtained from healthy and injured tissue samples (n=3). The fluid flow through the fibrous tissue is modeled based on Eringen's theory of micropolar fluid flow to determine the effects of vortex viscosity (m) and spin gradient viscosity (N) on hydraulic permeability. Results Computational results indicate that the hydraulic permeability of models which are replicates of healthy ACL tissues is higher than that of the injured, indicating that the filament size distribution might play an important role on fluid and nutrient transport through ligament tissues. Conclusions These findings underscore the need for increased attention on replicating the diameter distribution of healthy collagens in tissue engineering scaffolds and allowing adequate supply of elements through permeation during ACL reconstruction procedures.